2020
DOI: 10.1093/inthealth/ihz119
|View full text |Cite
|
Sign up to set email alerts
|

2030 Countdown to combating malnutrition in Burundi: comparison of proactive approaches for case detection and enrolment into treatment

Abstract: Background Burundi has one of the highest rates of malnutrition in the world, particularly chronic malnutrition, which affects 55% of all children <5 y of age. Although it rolled out a national treatment programme to combat all forms of malnutrition, enrolment of children remains difficult. In this study, we use observational data from two screening approaches to assess the effectiveness in detection and enrolment into treatment. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This indicates that the indicators of child nutritional status in Burundi were poorer than those of other countries in SSA. Previous studies have found a high prevalence of stunting, wasting, and underweight among children in Burundi [ 24 , 25 , 26 ]. Besides Burundi, the prevalence of wasting and underweight was highest in Burkina Faso and Chad.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the indicators of child nutritional status in Burundi were poorer than those of other countries in SSA. Previous studies have found a high prevalence of stunting, wasting, and underweight among children in Burundi [ 24 , 25 , 26 ]. Besides Burundi, the prevalence of wasting and underweight was highest in Burkina Faso and Chad.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important given that men and women participate at varying levels in bean production and marketing, and their active involvement can stimulate a more widespread adoption of newly released common bean varieties. For instance, in recent years, there has been much focus on breeding biofortified bean varieties to address the unending challenge of malnutrition in Burundi (Muroki et al, 2023; Odjidja et al, 2022). The breeding programs in Burundi have developed several biofortified bean varieties, including MAC44, RWV1129, RWV1272, NAKAJE, MAC70, MUHORO, RWR2154, and RWR2245 (Onyango et al, 2020).…”
Section: Introductionmentioning
confidence: 99%